Etnografi Komunikasi pada Tradisi Sedekah Ketupat di Desa Jambu Kecamatan Gelumbang Kabupaten Muara Enim - Ginting, Eraskaita; Ritonga, Muslimin; Safa Rora Amelia (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humani..., 2026)
The sedekah ketupat tradition in Jambu Village, Gelumbang District, Muara Enim Regency, is a local cultural practice preserved by the community as both an expression of gratitude and a medium for social interaction. Rather than a mere ceremonial activity, this tradition serves as a dynamic process of cultural communication, carrying rich symbolic meanings and social values passed down through generations. This study aims to examine the cultural communication process within the sedekah ketupat tradition and to identify its embedded symbolic meanings and cultural values. Utilizing a qualitative method with an ethnography of communication approach, data were collected through observation, in-depth interviews, and documentation, with informants selected via purposive sampling. The analysis applies Dell Hymes’ ethnography of communication theory, specifically the SPEAKING model, to explore the communicative elements of the tradition. Findings reveal that the communication process in the sedekah ketupat unfolds systematically through the stages of preparation, ritual enactment, and the distribution of the ketupat, incorporating verbal, nonverbal, and symbolic forms of communication. As a cultural symbol, the ketupat conveys historical, religious, and social meanings that are collectively understood by the community. Furthermore, this tradition reflects the values of togetherness, mutual cooperation, and reverence for ancestors, thereby functioning as a vital medium of cultural communication in sustaining the community's social values and cultural identity.